Quantization of the Electric Conductivity in Carbon Nanotubes - M. A. Grado-Caffaro; M. Grado-Caffaro (Active and Passive Electronic Components)
In this paper, the electric conductivity of carbon nanotubes is investigated by deriving a mathematical expression for the quantized conductance in an ideal one-dimensional potential well with a single electron moving in it. Our results are compared with experimental data.